THE EXISTENCE OF LIVING LAW IN CRIMINAL LAW REFORM: EXPANSION OF THE PRINCIPLE OF LEGALITY - Dwi Kurniawan, Itok (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
The implementation of WvSvNI as a rule of criminal law in Indonesia after the proclamation of independence of the Republic of Indonesia automatically enforces the principle of formal legality embedded in it. The principle of formal legality is rigid because it places criminal law as the only basis for punishing someone's actions for an act regulated therein. The principle of formal legality also negates the existence of living law in Indonesian society, which is often known as customary law. Criminal law reform through the ratification of the National Criminal Code seeks to integrate living law as a source of criminal law. This article will discuss issues related to the existence of living law (Adat law) in the renewal of national criminal law. The method used in this legal research is a normative legal research method with a statutory approach. The results of this study indicate that the inclusion of living legal provisions (Adat law) into criminal law is an effective effort to achieve comprehensive justice for the Indonesian people, the actual form of which is to protect society (especially victims) from actions that are detrimental to themselves. Society is protected from not only mala prohibita acts but also extraordinary criminal acts, one of which is customary crime.